(untitled) (Olhar de Professor, 2023)
The present text deals with the movements of disputes in the field of educational policy, focusing on the documentary analysis of the versions of the National Common Curricular Base (BNCC) - Early Childhood Education (EI) as a producer of resistance to conservative curricular proposals. The analyzes are linked to the studies by Picoli (2020), Biesta (2017) and Barbosa, Cruz, Fochi and Oliverira (2016). In view of the analyzed content, it is understood that the period of construction of the BNCC was marked by disputes, changes in the speeches and changes in the agents who participated in the commissions, such changes were anchored to neoliberal and conservative movements, which followed the proposal of competences and skills. In this context, Early Childhood Education as part of the Base proposed resistance movements, rethinking the curricular logic beyond content or skills and abilities, proposing teaching / learning based on the experience and relationships between children and society.